2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26349
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and Retention of Inner-city Under-represented Minority Students for Careers in STEM: Parent Perspectives

Abstract: The objective of this work is to identify the likely barriers to STEM success for students and parents within a specific inner city culture, provide a deeper understanding of these barriers and to suggest a solution that strategically removes or neutralizes these barriers. Surveys were issued to parents in the local community in order to gather opinions on the relevance of conventional questions and solutions suggested by the literature for this national problem. We hypothesized that, (i) not all research base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Involvement of parents in engineering workshops and camps may be even more important for under-represented groups within engineering, as those students are less likely to have familial exposure to engineering. Research has shown that inner city under-represented minority parents are interested in STEM for their kids, but are often less aware of opportunities and also have barriers to participating in the activities [30]. As mothers (at least in Black families) have greater influence than fathers on academic identity development [17], targeting parental interventions (intended to increase parental awareness of engineering as a profession) at mothers may be more effective than targeting fathers, especially for under-represented minority students.…”
Section: Recommendationsmentioning
confidence: 99%
“…Involvement of parents in engineering workshops and camps may be even more important for under-represented groups within engineering, as those students are less likely to have familial exposure to engineering. Research has shown that inner city under-represented minority parents are interested in STEM for their kids, but are often less aware of opportunities and also have barriers to participating in the activities [30]. As mothers (at least in Black families) have greater influence than fathers on academic identity development [17], targeting parental interventions (intended to increase parental awareness of engineering as a profession) at mothers may be more effective than targeting fathers, especially for under-represented minority students.…”
Section: Recommendationsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] The main reasons for students not enrolling are program costs and a lack of program availability, both of which were cited to be higher in rural areas. 14,15,21,22 Along with funding challenges, some programs are also not aligned with students interests, with only half of them offering stimulating STEM activities. 14,21 In order to allow for both more rigorous STEM involvement and to reach even more students, universities are looked to for additional programs.…”
mentioning
confidence: 99%
“…14,15,21,22 Along with funding challenges, some programs are also not aligned with students interests, with only half of them offering stimulating STEM activities. 14,21 In order to allow for both more rigorous STEM involvement and to reach even more students, universities are looked to for additional programs. As a result, universities typically offer summer programs to high school students that allow them to explore STEM topics as laboratories and classrooms are utilized during the school year by undergraduate and graduate students.…”
mentioning
confidence: 99%
See 1 more Smart Citation